ANALISIS KEBERADAAN SEKTOR EKONOMI KABUPATEN/KOTA DI PROVINSI BALI - Putri, Vivi Erlinda Thio; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
The economic potential of an area is the economic capacity that is in the area that is possible and feasible to be developed, so that it will continue to develop as a source of livelihood for the local people. This study aims to 1) analyze the potential sectors in districts / cities in the Province of Bali, and 2) analyze the relationship of economic growth with economic potential in districts / cities in the Province of Bali. The data source used this study is secondary data with 54 observations. This study uses a non-behavioral observation data collection method. Data analysis techniques used in this research are Location Quotient (LQ), and simple regression analysis. The results showed that (1) Bali Province has 4 regencies whose average is included in the potential sector, these districts are Jembrana Regency, Badung Regency, Klungkung Regency, and Karangasem Regency. Potential economic sectors in the four districts are agriculture, forestry and fisheries; mining and excavation; water supply, waste management, waste and recycling; construction; processing industry; transportation and warehousing; wholesale and retail trade; car and bicycle repair; providing accommodation and eating and drinking. (2) Economic growth has a positive effect on economic potential in Bali's regencies / cities. Keywords: potential sector, regional potential, economic growth